707 Dermal absorption of fluoride and hydrogen ions following topical exposure to hydrofluoric acid. (24th April 2018) - Kilo, Sonja; Dennerlein, Kathrin; Korinth, Gintautas; Göen, Thomas; Drexler, Hans
Abstract : Introduction: Despite being an extremely hazardous liquid, hydrofluoric acid (HF) is commonly used in industry due to its unique chemical properties. Chemically HF is defined as a 'weak' acid but fluoride ions can induce serious systemic toxic effects. Upon contact with low concentrated HF, symptoms such as pain or local lesions may be delayed. The aim of this study was to characterise changes in intradermal pH and dermal fluoride penetration following HF application. Methods: A static diffusion cell model was used to study dermal fluoride penetration for 6–72 hour following application of varying amounts of HF (c=5%–50%, 100–160 µl/0.64cm 2, 1–10 min.) on human skin (thickness 0.9 or 2.5 mm). Intra- and transdermal amounts of fluoride and intradermal pH were determined. Result: Transdermal penetration of fluoride increased exponentially with increasing HF concentration. In addition, penetration increased four-times by extending the exposure time from 1 to 3 min. No further increase was seen with longer HF application (5 and 10 min.). The increased amount of HF penetrated through 0.9 mm compared to 2.5 mm skin within one hour was levelled out at later time points. Intradermal accumulation of fluoride increased dose-dependently but to a lower degree. Intradermal pH dropped with increasing HF concentration and exposure time. Additionally, the lag time between HF application and onset of pH changes decreased with increasing HF concentration and application time. Discussion: The results of the present study show that following 3 min. HF application maximal amounts of fluorides seem to have penetrated the skin. The longer lag time in pH drop with lower concentrated HF might explain the delay between HF contact and onset of pain.